Highlights from Livestock, Gender, and Agency Amid Conflict in Ethiopia - CGIAR System Organization (CGIAR System Organization, 2024)
This video presents the highlights of the Conference on “Livestock, Gender, and Agency Amid Conflict in Ethiopia” on December 11, 2024 at the ILRI Campus in Addis Ababa. The event, jointly organized by CGIAR Research Initiative on National Policies and Strategies (NPS), along with the Policy Studies Institute (PSI), International Food Policy Research Institute (IFPRI), and International Livestock Research Institute (ILRI), where experts shared research on the intersection of livestock systems, gender dynamics, and resilience during conflict. Explore how these findings illuminate challenges and opportunities for empowering communities in Ethiopia’s evolving agricultural landscape.